Safety and efficacy of transarterial chemoembolization combined with tyrosine kinase inhibitors and camrelizumab in the treatment of patients with advanced unresectable hepatocellular carcinoma - Li, Jinpeng; Kong, Mingxin; Yu, Guangji; Wang, Song; Shi, Zhaozhang; Han, Huihui; Lin, Yanyan; Shi, Jutian; Song, Jinlong (Frontiers in Immunology, 2023)
Objective: This study was aimed to evaluate the efficacy and safety of transarterial chemoembolization combined with tyrosine kinase inhibitors and camrelizumab in the treatment of unresectable hepatocellular carcinoma and to explore a new therapeutic strategy for the treatment of advanced HCC.A total of 87 patients aged 18-75 years with at least one measurable lesion per Response Evaluation Criteria in Solid Tumors (version 1.1) were included in the study. TACE was administered as needed, and camrelizumab and TKI medication were initiated within two weeks and one week after TACE, respectively. The primary endpoints were progression-free survival and objective response rate .The 87 patients in this trial were last evaluated on September 28, 2022, and 35.8% were still receiving treatment at the data cutoff. A total of 34 patients (39.1%) died, and the median OS was not reached. The median PFS was 10.5 months (95% CI: 7.8-13.1). The ORR rate was 71.3% (62/87), and the DCR rate was 89.7% (78/87) per mRECIST. According to RECIST version 1.1, the ORR rate was 35.6% (31/87), and the DCR rate was 87.4% (76/87). Ten patients (11.5%) successfully underwent conversion therapy and all achieved R0 resection. Two patients achieved a complete pathological response, four achieved a major pathological response, and four had a partial response .All treatment-related adverse events were tolerated. No serious adverse events were observed, and no treatment-related deaths occurred.Conclusions: TACE combined with TKI and camrelizumab was safe and effective in treating advanced HCC. Triple therapy may benefit patients with large tumor burden and portal vein cancer thrombus and is expected to provide a new treatment strategy for advanced HCC.